Hormonal determinants of prehypertension in a random sample of St. Petersburg residents: data from the ESSE-RF study - A. M. Erina; M. A. Boyarinova; E. V. Moguchaya; E. P. Kolesova; E. Yu. Vasilyeva; A. S. Alieva; N. A. Paskar; O. P. Rotar; E. I. Baranova; A. O. Konradi; E. V. Shlyakhto (Российский кардиологический журнал, 2021)
Aim. To determine the association of prehypertension (PHTN) with cardiometabolic and hormonal factors in a population sample of St. Petersburg residents.Material and methods. As part of the ESSE-RF epidemiological study, a random sample of 1600 residents of St. Petersburg at the age of 25-64 was examined. All participants signed informed consent and completed the questionnaires. Anthropometry, fasting venous blood sampling, blood pressure (BP) measurements were performed. BP was measured by the OMRON BP monitor (Japan) twice on the right hand in a sitting position. Mean BP was calculated. Respondents, depending on the BP level and availability of antihypertensive therapy, were divided into 3 groups: optimal BP (<120/80 mm Hg), PHTN (120-139/80-89 mm Hg) and HTN (≥140/90 mm Hg or antihypertensive therapy). Blood levels of insulin, N-terminal pro-brain natriuretic peptide (NT-proBNP), thyroid-stimulating hormone, C-reactive protein (CRP), morning cortisol, leptin, adiponectin were assessed. The insulin resistance index was calculated using the Homeostatic Model Assessment (HOMA) according to the following equation: glucose (mmol/l) × insulin (μIU/ml))÷22,5. Mathematical and statistical data analysis was carried out using the SPSS Statistics 26 program.Results. The data from 1591 participants were analyzed. Among the surveyed persons, women predominated (n=1025; 64,4%). With BP increase from optimal to PHTN, HTN, the levels of CRP, insulin, HOMA-IR and leptin increases in male and female respondents. In addition, there is an increased prevalence of hyperinsulinemia and insulin resistance in the female population. Multiple logistic regression, adjusted for sex, age, obesity ( body mass index ≥30 kg/m2) and waist circumference (≥102 cm for men and 88 cm for women), revealed associations of PHTN with an increase in insulin >173,0 pmol/L (2,99 [1,22; 7,36], p=0,017), HOMA-IR >2,9 (2,12 [1,42; 3,19], p<0,0001) and associations of HTN with an increase in insulin >173,0 pmol/L (2,14 [1,30; 3,54], p=0,003), HOMA-IR >2,9 (1,83 [1,39; 2,42 ], p536 nmol/L (1,59 [1,25; 2,05], p125 pg/ml (2,05 [1,32; 3,20], p=0,002).Conclusion. In a random sample of St. Petersburg residents, the presence of hyperinsulinemia increases the risk of PHTN and insulin resistance by 3 and 2 times, respectively.